A super energy transfer process based S-shaped cluster in ZnMoO4 phosphors: theoretical and experimental investigation. Issue 32 (28th August 2015) - Ran, Weiguang; Wang, Lili; Zhang, Wenwen; Li, Feiyang; Jiang, Haiyan; Li, Weina; Su, Linghao; Houzong, Ruizhi; Pan, Xiaohua; Shi, Jinsheng
<x xml:space="preserve">Abstract</x> In the ZnMoO4 phosphor, Bi3+ and Eu3+ ions were trapped together in an S-shaped cluster. A super energy transfer process from Bi3+ to Eu3+ occurred due to their short distance.